Biotechnological method of the synthesis of new ribavirin structural analogs. - I. V. Fateev; I. D. Konstantinova; V. I. Shvets (Тонкие химические технологии)
Modern effective biotechnological method of the synthesis of new analogues of 1-β-D-ribifuranozyl-1,2,4- triazole-3-carboxamide (ribavirin) from 3-amino-1,2,4-triazole was developed. Gene-engineering enzymes purine- and, thymidine phosphorylasis were used for biothecnological method of the synthesis ribavirin analogs.